Non-catalytic tyrosine-phosphorylated receptors. - Dushek, O; Goyette, J; Van Der Merwe, P (2012)
Leukocytes play a critical role in recognizing and responding to infection and cancer. Central to this function is an array of cell-surface receptors that lack sequence homology. Many of these receptors have in common the fact that their signaling involves phosphorylation of cytoplasmic domains by extrinsic tyrosine kinases. These non-catalytic tyrosine-phosphorylated receptors (NTRs) share a number of other features, including small size and optimal stimulation by surface-associated ligands. We argue here that NTRs are also likely to share the same kinetic-segregation triggering mechanism, which involves segregation of the engaged NTR from receptor tyrosine phosphatases with large ectodomains such as CD45 and CD148. NTRs signal through tyrosine-containing cytoplasmic motifs, which recruit distinct cytoplasmic signaling proteins when phosphorylated, transducing activatory or inhibitory signals. They have two features that make them uniquely well suited to their role in immune recognition of infection and cancer. Their modular structure enables the coupling of many rapidly evolving receptors with diverse ligand specificities to the same conserved signaling machinery. Their similarity in size and shared signaling machinery enables them to colocalize at cell-cell interfaces when they engage ligands, facilitating the integration of activatory and inhibitory signals from multiple receptors at the cell surface.